Modelling the chlorine dispersion from hypothetical leak in kasigui water treatment plant - Wang, Zhi Lei; Low, Jia Yi; Chin, Siew Choo; Jolius, Gimbun (UTM Press, 2025)
The dispersion of a hypothetical chlorine leak from the Kasigui water treatment plant was modeled using the Areal Locations of Hazardous Atmospheres (ALOHA) software. Meteorological data, including wind speed, direction, and time, were obtained from the local weather station through the Malaysian Meteorological Department for the simulation. The effect of wind conditions on the chlorine dispersion was evaluated using both the Gaussian plume and heavy gas models. The local concentration and threat zones were mapped using the Mapping Application for Response, Planning, and Local Operational Tasks (MARPLOT) software, with the aid of OpenStreetMap. The results showed that the residential areas surrounding the plant, including Taman Kasigui, Taman Desa Manis Kasigui, Kg Kibabaig, Kg Tuavon, Kg Nampasan, the Sabah Cultural Center, Jabatan Pertanian Penampang, the Penampang District Council, and Kg Dabak, were affected by a dangerous chlorine dispersion, as indicated by 60 minutes Acute Exposure Guidelines Level 3 (AEGL-3)(> 20 ppm). Suitable safety evacuation routes were proposed to reduce the risk of exposure to hazardous gas. The findings from this work are useful for understanding the risks of chlorine gas dispersion around the Kasigui water treatment plant.